The Role of Christian Religious Education: Strengthening Teenagers' Christian Identity Amidst the Influence of Social Media - Rosnila Hura (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The Role of Christian Education: Strengthening the Christian Identity of Teenagers in the Midst of the Influence of Social Media. Social media has become an integral part of teenagers' daily lives and affects the way they interact, think, and shape self-identity. In this context, the Christian identity of teenagers faces increasingly complex challenges due to various digital content that is not always in line with the values of the Christian faith. Although there is a lot of research on Christian education, empirical studies that specifically examine the role of Christian Education in strengthening the Christian identity of teenagers in the digital era are still limited. This research aims to describe the influence of social media on Christian teenagers and examine the role of Christian Religious Education in strengthening their Christian identity. This research uses a descriptive quantitative approach with the survey method. The data was collected through a Likert scale questionnaire given to 120 Christian teenagers in Mojokerto Regency and analyzed using descriptive statistics in the form of a percentage. Research results show that social media has a positive and negative influence on the formation of adolescent Christian identity. In addition, Christian Religious Education plays an important role as a protective mechanism in strengthening the identity of youth's faith through the formation of faith awareness, critical attitude, and moral steadfastness in facing the challenges of the digital world.